Carbon‐Network‐Integrated SnSiOx+2 Nanofiber Sheathed by Ultrathin Graphitic Carbon for Highly Reversible Lithium Storage. Issue 10 (1st March 2016) - He, Haiyong; Kong, Debin; Wang, Bin; Fu, Wei; Qiu, Xiongying; Yang, Quan‐Hong; Zhi, Linjie
Abstract : Graphitic carbon is grown on SnSiO x +2 nanofibers to obtain nanocables, into the core of which carbon network and atomic‐level dispersion of SnO x were embedded. The resultant nanocables with a highly conductive carbon framework exhibit outstanding cycling performance with high specific capacity and excellent cycling stability even at high current rates.